Persepsi Ibu Balita tentang Stunting di Wilayah Puskesmas Tarus Kabupaten Kupang - Sisilia Noviaming; Afrona E. L. Takaeb; Helga J. N. Ndun (Universitas Nusa Cendana, 2022)
Perception of mothers is one of the important aspects in overcoming stunting. The purpose of this study was to examine the perceptions of mothers under five about stunting in the Tarus Community Health Center. The research was qualitative research with a phenomenological approach. Data collection by in-depth interviews with 6 mothers of stunted toddlers. The research was conducted in November 2020. The results showed that the perception of mothers under five about stunting is still limited. Mothers perception of the notion of stunting was limited to physical appearance only, such as small figure of children, slow growth, short stature, thinness, weakness, and malnutrition.The impact is prone to illness, weakness, lack of enthusiasm, laziness to move, physical disabilities and reduced children's grasping power. Direct causes of stunting in children not breastfed, not immunized, worms, malnutrition, mothers not consuming nutritious food during pregnancy, premature birth and genetic factors. Efforts to prevent and control stunting byproviding nutritious food and marungga vegetables, routine health checks, exclusive breastfeeding, posyandu, and inviting children to do activities. Informants did not state that environmental factors such asclean water and sanitation is a indirect cause of stunting in children. Prevention and control of stuntingonly focuses on specific nutrition interventions such as food intake and routine health checks at posyandu, but ignores sensitive nutrition interventions, namely clean and healthy lifestyle. Suggestion: it is necessary to do socialization about stunting and its handling through specific interventions and sensitive interventions.